Slotted UHF RFID full embroidery e-textile wearable tag antenna for WBAN application - Dawood, Bahaa Abbas (2017)
RFID stands for Radio Frequency Identification. The major purpose that RFID system is built for is to transfer data on a transponder (tag) that can be regained with a transceiver by means of a wireless connection. The contactless Identification (ID) system depends on data transmission by radio frequency electromagnetic (EM) signals, and accordingly, the whole functionality is weather independent and non-lineof- sight. These features for ID system copes the optical barcodes limitations, which are weather dependent, line-of-sight, and manual operation requirement. Most of RFID tags consisted of integrated circuit (IC) or a Chip and an antenna. The IC executes all of the data processing and is energized by extracting the power from the interrogation signal transferred by the RFID reader. The tag antenna controls the amount of power transmitted from the reader to the tag and the reflect signal from the tag to the reader. Nevertheless, there are no restrictions on the physical parameters of the readers antenna, such as being small or planar in size, these restrictions do stratify on the tags antenna. In a matter of fact, the tag miniaturizing in size is limited by the tag antenna size. Wearable antenna is described as an antenna designed to be an integral part of garment to be worn on the body. The use of radios and antennas in clothing are less cumbersome to the handler compared with traditional handheld whip and radios antennas due to its advantages in long-term use. Wearable antennas were first adopted for home-nursing, hospital patient clothing and clothes rescue workers. This thesis reports on the design, fabrication, and measurement of Ultra High Frequency (UHF) RFID tag antennas (860 to 960 MHz), which can be used in bodycentric applications. The introduced tag antennas are designed and fabricated to accomplish low tagging costs, good performance, as well as tagging Wireless Body Area network (WBAN) objects with small size tags. First, full embroidery electro textile RFID tag antenna was designed and tested. In this design, a slotted small size antenna is proposed and designed for wearable bodycentric objects UHF RFID (860-960) MHz. The antenna structure embroidered on %100 Polyester as a substrate. Furthermore, E-shaped inductive feeder consists of two opposing symmetrical E-shaped structures to feed the top radiator for antenna. The antenna size is 74×20×2.75 mm3 at 915 MHz. The peak gain for the antenna reached to 0 dBi at 915 MHz. The antenna bandwidth is 19 MHz (908-927) MHz (power reflection coefficient lower than -3 dB). The measurement result shows very good impedance matching due to the flexibility given by the E-shaped slotted inductive feeder; moreover, there is a very good agreement with simulations results. The design shows a good gain and good performance. This antenna introduced to fill up the need for tagging for long range and mounted for body-centric objects such as access tagging integrated with clothes and in healthcare system.